Complex hierarchy: The strategic advantages of a trade-off between hierarchical supervision and self-organizing. Issue 2 (April 2015) - Accard, Philippe
Abstract This paper presents two case studies of research labs in which changes implemented in hierarchical structures differ from the delayering and downsizing reported by current empirical works. In both labs, authority relationships between superiors and subordinates relaxed and became indirect and recursive. Then, together, superiors and subordinates engaged in self-organizing processes and produced structures that had emergent characteristics. The hierarchical structures that were produced exhibited the characteristics of complex organization structures. The conceptualization of these changes, developed in this paper, provides a better understanding of hierarchical structures and authority in complex organization. It invites a reconsideration of the idea that hierarchy inevitably hinders organizational change, and it indicates possibilities for a trade-off between hierarchic supervision and self-organizing. This trade-off provides strategic advantages by helping managers develop organization capacity for learning, innovating, and performing adaptive changes.